Negotiating Femininities in the Neoliberal Night-Time Economy Too Much of a Girl? - Nicholls, Emily (Genders and Sexualities in the Social Sciences, 2019)
This book explores the ways in which young women negotiate gendered and classed identities in nightlife venues. With a particular focus on the under-researched phenomenon of the 'girls' night out', this text explores tensions around what it means to be 'girly' in bars, pubs and clubs, examining throughout the ways in which being a 'girly girl' is simultaneously desired and derided in a postfeminist context. Drawing on research conducted in Newcastle-upon-Tyne, UK, this original and comprehensive book explores the value and meaning of the 'girls' night out' for young women, and its instrumental role in the negotiation of friendships and femininities. Nicholls covers a range of themes, including alcohol consumption, dress, and risk management, providing engaging and timely insights into women's leisure as a site for the negotiation of gendered identities. Negotiating Femininities in the Neoliberal Night-Time Economy will be of interest to students and scholars acrossthe social sciences with an interest in gender, class and the Night-Time Economy.